The narrations of saeed bin al musayyab about the holy twelve Imams in the books of public and imani (Journal of Imam Al-Kadhim College, 2024)
Praise be to God, who is worthy of praise, thanks, prayers and peace be upon Muhammad, may God bless him and his family, the best of God’s creation, and upon his family and those who followed him, supported him, and were loyal to his family, supported them, followed their path, and adhered to them.                                                 Now then... This research entitled The Shining Anecdotes of the Illuminating Narrations of Saeed bin Al-Musayyab about the Twelve Purified Imams, in which I dealt with collecting and studying selected narrations of the noble companion Saeed bin Al-Musayyab about the pure Imams, peace be upon them, that reached us and we researched their contexts that were mentioned through hearing or transmission of the companion Saeed bin Al-Musayyab, and the prominent role his Shiism played in that era and his standing with the truth and his exposure to various types of harm, as stated in the Almighty’s saying: (O you who believe, fear Allah and speak words of appropriate justice. He will amend for you your deeds and forgive you your sins. And whoever obeys Allah and His Messenger has certainly attained a great attainment, these noble verses show us that they include three important matters, which are correctness, guidance and righteousness, in which the statement that matches reality and is not idle or of illegitimate benefit are combined. The believer is charged with testing the truth of what he says and not corrupting the actions, so adhering to the correct statement leads a person to the righteousness of actions .Despite the efforts made by modern scholars in the renaissance of truth and its establishment and support of the Ahl al-Bayt, peace be upon them, we still need more, as there are still aspects that lack increase and research. One of the topics that need research and study is the topic of the narrations of the Companions, may God be pleased with them, who supported and supported the Ahl al-Bayt, peace be upon them, and transmitted to us their narrations from their grandfather, the Noble Prophet, may God bless him and his family
Keywords: Narrations / Saeed bin al-Musayyab / The holy Imams. Imam zain alabden(as)